Application of markers of collagen metabolism in serum and synovial fluid for assessment of disease process in patients with rheumatoid arthritis. Issue 11 (November 1995) - Hakala, M; Aman, S; Luukkainen, R; Risteli, L; Kauppi, M; Nieminen, P; Risteli, J
Abstract : OBJECTIVE–To assess the potential of markers of collagen metabolism to reflect disease processes in rheumatoid arthritis (RA). METHODS–Serum (S) and synovial fluid (SF) from 59 patients with RA, and a knee joint effusion and serum from 90 control subjects were studied with radioimmunoassays for the aminoterminal propeptides of type I and type III procollagens (PINP and PIIINP, respectively). The breakdown of type I collagen was quantified with a radioimmunoassay for the cross linked carboxyterminal telopeptide of type I collagen (ICTP). RESULTS–About 50% of the patients had increased S-ICTP and S-PIIINP values, whereas S-PINP was increased in only 20% of the patients. The mean SF:S ratios of these markers varied between 4 (for ICTP) and 340 (for PIIINP), indicating that markers of collagen metabolism are formed locally and then released into the circulation. SF-PINP and SF-PIIINP correlated with each other (rs = 0.86, p < 0.001) and with SF-ICTP (rs = 0.69, p < 0.001, and rs = 0.65, p < 0.001, respectively). SF-ICTP was clearly related to radiographic findings in the corresponding knee joint, patients with gross bone deformation having the greatest SF-ICTP concentrations. S-ICTP and S-PIIINP also correlated with conventional markers of disease activity, such as C reactive protein and joint swelling score. CONCLUSION–Markers of collagen metabolism both in serum and synovial fluid can be measured to provide an assessment of disease process in patients with RA. ICTP and PIIINP are the most informative.